Penerapan Ajaran Tri Kaya Parisudha Dalam Pembentukan Perilaku Yang Baik Terhadap Peserta Didik - Luh Putu Novi Ernawati (Jayapangus Press, 2018)
Religion is a quest for mankind in God. Throughout the ages, mankind has always wrestled in its quest for the secrets and the essence behind this life, religion is a means or a way to bridge and provide solutions to solve a problem in this life. There are many ways to reach the ultimate truth: do not hurt anyone, then follow your teacher sincerely, who has the intention of not engaging in conflicts, appreciate unity in difference, the difference is wonderful if you can understand.